Um estranho em casa? Casamento, gênero, imigração e interculturalismo em Aracaju - Araújo, Liliana Aragão de (2021)
In the connection between the decolonial theory of gender and interculturality, this research seeks to answer the following starting question: how are the social roles of gender constructed in intercultural marriages, between Brazilian women and immigrant men living in Aracaju? In order to do so, I drew with a general objective to understand how the social roles of gender are constructed in intercultural marriages between Brazilian women and immigrant men residing in Aracaju; and as specific objectives: to identify how the transmission of family rituals in families with spouses of different nationalities is processed; understand what are the preexisting social representations about the foreign man and the Brazilian woman; analyze how power relations occur in the daily decisions of these relations; investigate whether in these conjugal relationships the social roles historically constructed between men (public space) and women (private space) are repeated; investigate what are the disputes and tensions of these relationships. The option of naming intercultural marriages, having as a focus, in this thesis, people of different nationalities, mother tongues and cultural background, is based on an understanding of the differences and inequalities of these relationships, and understanding that they – the differences and inequalities – they restore power relations and hierarchies that are often made invisible. For that, I conducted interviews with nine couples of different nationalities residing in Aracaju, it is important to point out that all men have different native countries. These interviews were carried out at the couple's residence, at the store or in some environment indicated by the interviewees. I used the oral history technique, through a semistructured interview, and obtained authorization to record all interviews. Despite the heterogeneity of the sample, I observed that the social construction of gender roles in intercultural relations preserves the characteristics of male domination and power asymmetries between men and women. However, when articulated to other identity markers such as race, class, educational level, there are more egalitarian relationships, as women have more economic autonomy, are in their native country, with their native culture, their families and friends.